(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Gunawan H, Iskandar S, Sihombing VS, Wienanto R. 2017. Conflict between humans and leopards (Panthera pardus melas Cuvier, 1809) in Western Java, Indonesia. Biodiversitas 18: 652-658. Conflict between the Javan leopard (Panthera pardus melas Cuvier, 1809) and humans occupying the same region have tended to increase in the last decade in proportion to increase in deforestation followed by fragmentation and habitat loss. The objectives of this research were to study the leopard-human conflict and to analyze the causes in order to formulate recommendations for mitigation. Literature study, structured interviews, and field surveys were carried out to collect data on leopard-human conflict. Spatial modeling using weighted overlays generated a map of conflict potential in Western Java. The results showed that in the last 15 years 71 cases of leopard-human conflict had been recorded, with a tendency to increase over time. There have been 75 records of occurrence of the Javan leopard population in Western Java, of which 30% are assessed to have had a high potential for conflict; 25% had moderate potential, and 46% had low potential. There are indications that leopard-human conflict has occurred in villages around degraded forest areas due to human encroachment and cultivation. Consequently, a special forest management strategy must be implemented on a landscape scale, crossing the boundaries of conservation forest, productive forest, protected forest and other land uses.